Worldwide burden of gastric cancer in 2012 that could have been prevented by increasing fruit and vegetable intake and predictions for 2025 - Peleteiro, B (2016)
The regional and temporal variation in patterns of fruit and vegetable intake contributes to differences in the impact on gastric cancer burden across regions and over the years. We aimed to estimate the proportion and absolute number of gastric cancer cases that could have been prevented in 2012 with an increase in fruit and vegetable intake up to the levels defined by the Global Burden of Disease as the theoretical minimum-risk exposure distribution (300 and 400 g/d, respectively), as well as the corresponding figures expected for 2025. Preventable fractions (PF) were computed for 161 countries, using data on fruit and vegetable availability in 1997 and 2010 and published estimates of the magnitude of the association between fruit and vegetable intake and gastric cancer, assuming a time lag of approximately 15 years. Countries classified as very high Human Development Index (HDI) presented median PF in 2012 much lower than low-HDI countries for both fruits (3.0 v. 10.2%, P<0.001) and vegetables (6.0 v. 11.9%, P<0.001). For vegetables only, PF significantly decreased until 2025 in most settings; however, this corresponded to a reduction in the absolute number of preventable gastric cancer cases in less than half of the countries. Increasing fruit and vegetable intake would allow preventing a relatively high proportion of gastric cancer cases, mostly in developing countries. Although declines in PF are predicted in the near future, changes in order to achieve healthier lifestyles may be insufficient to overcome the load of demographic variation to further reduce the gastric cancer burden.